Effect of van der Waals interactions on the adhesion strength at the interface of the hydroxyapatite–titanium biocomposite: a firstprinciples study - Grubova I. Yu. Irina Yurievna; Surmeneva M. A. Maria Alexandrovna; Surmenev R. A. Roman Anatolievich; Neyts E. C. Erik (2020, 2020)
Title screen